Preparation and densification of bulk pyrite, FeS2. (December 2021) - Ferreira, Helena M.; Lopes, Elsa B.; Malta, José F.; Ferreira, Luís M.; Casimiro, Maria Helena; Santos, Luís F.; Pereira, Manuel F.C.; Moço, Duarte; Gonçalves, António P.
Abstract: A favourable electronic structure, together with a high abundance of pyrite (FeS2 ) in the Earth's crust, make this sulfide a promising material for thermoelectric applications. However, the experimental work published to date underlines a challenging scenario, with FeS2 presenting systematically small power factors. Knowing that sulfur vacancies are a key aspect for controlling the electronic transport properties of FeS2, this work focuses on the preparation of pyrite by hot-pressing and entails a careful characterization of its microstructure, chemical composition, thermal stability, and electrical transport properties. Dense pellets (>90% of the theoretical density) were obtained, consisting mostly of pyrite with trace amounts of Fe7 S8 . Different hot-pressing conditions led to similar chemical compositions, with no significant lattice distortions. Pyrite proved to be thermally stable up to 400 °C under an inert atmosphere. Analysis of the electronic band structure and density of states by density functional theory implies a p-type semiconductivity. However, measurements of Seebeck coefficient indicated n-type semiconductivity for pyrite produced by this experimental procedure. The highest power factor measured in this work, 0.23 μW K −2  m −1, is still far from what can be considered a promising value for thermoelectric materials, but different ways of improving it are discussed. Highlights: The use of hot-pressing to obtain bulk pyrite samples has been tested. Dense materials were obtained under the optimized consolidation conditions. The increase in density increases the electrical conductivity of pyrite. No evident direct correlation between Seebeck coefficient and density was seen.